Investing in lean to improve basic capabilities: A strategy for system supply? - Inga-Lill Carlsson; Håkan Aronsson (Journal of Industrial Engineering and Management (JIEM), 2017)
Purpose: This paper describes the perceived effects of implementing lean production in a Swedish SME contract manufacturer. Especially focused are the effects on, and possible trade-offs between, cost-efficiency and flexibility. Design/methodology/approach: SME suppliers need basic capabilities of qualitative production performance which may then be stepping-stones to develop more system supplier capabilities for added customer value: leadership to manage systems and processes, SCM, communications and relations management. Development of stable production processes is seen as a way to reach stable basic performance, efficient and with higher resource utilization. Quality is a precursor to delivery performance as well as to cost reduction and flexibility. This is a longitudinal single case study of a SME supplier striving to become a system supplier. Two main sources of data collection are used: interviews and the main author's presence as employee and business developer, participating in and following up the ongoing change process. Findings: Two specific findings appeared: (1) An initial effect was an important "eye-opener" for the balance between cost efficiency and flexibility in the organization. (2) Process orientation, as the basis of both lean and agile approaches, allows many improvements without any conflicts or trade-offs between these two goals. Stability in the production leads to increased controllability, initially resulting in both higher cost-efficiency and higher flexibility. As the organization develops however, strategic considerations relating to the chosen market strategy might occur: cost leadership or differentiation. Research limitations/implications: These results reflect the experiences of one SME supplier and further studies are needed for generalizability. Originality/value: The study increases the understanding of how a SME may develop stable processes in its different supplier-customer contexts. The study points at some necessary basic components of this process approach as a first step for the transition to system supplier.
Keywords: 650; SME; system supplier capability; lean production; agility; stable processes